THE COMPARISON OF FINITE ELEMENT METHODS TO INVERSE DISTANCE SQUARE AND NATURAL NEIGHBOR FOR RESOURCE ESTIMATION OF LATERITIC NICKEL DEPOSIT - ALEX HARMOKO (NIM : 22106310), ANTONIUS
This research is aimed at introducing an alternative concept on resource calculation deterministically with a case study at the lateritic nickel deposits using Finite Element Methods (FEM). The Case study in this research is for lateritic nickel deposit at Mandiodo, Konawe Utara, South - East Sulawesi Province. FEM is a deterministic method that is able to show good visual model or conceptual that representing mathematical model, attaining mathematical model to numerical model, estimating accurate state variable distribution, is been widely used, and it is user friendly. In this research, FEM was compared to other deterministic methods which are commonly used in resource estimation, those are: Inverse Distance Square (IDS), and Natural Neighbor. Lateritic nickel resource estimation has been performed by using borehole data, with distance 50 metres space between boreholes, composited to detemine economic lateritic nickel zone, as: limonit and saprolit, that reached the parameter of top and bottom zone, thickness, and Ni characteristic at each zones. The data then was estimated and calculated from the resources of each zone by using those three methods. The error estimation from the methods subsequently was analyzed by using Mean Square Error (MSE) and Scatter Plot Diagram. The result of these resources estimation at the research location with the three methods has shown close results. Accuracy of the three methods analyzed by MSE and Scatter Plot Diagram presented a result that FEM estimation provided better result, as shown from relatively smaller MSE and relatively larger coefficient of corelation (≈R) comparing to IDS and Natural Neighbor methods. Thus, FEM can construct a better geometry of lateritic nickel deposits than IDS and Natural Neighbor, hence it can be gathered a more accurate resource calculation. The weaknness of FEM appears when we try to approach geometric form with high accuracy, it takes many numbers of elements to use that numerically needs longer calculating process and better computer performance.